Pengaruh Model Pembelajaran Reciprocal Teaching Berbasis Penilaian Kinerja Terhadap Kompetensi Pengetahuan IPA - ni ketut feby puspita; i wayan darsana; i b g s abadi (Universitas Pendidikan Ganesha, 2018)
This study aimed to know about the affect of reciprocal teaching model based on performance assessment againts the competence science knowledge of fourth grade students of elementary school Gugus I Gianyar district in 2017/2018. This research type is quasi experiment research with nonequivalent control group design. The population of this study is all students of class IV elementary school Gugus I Gianyar district which 440 students. Sample were taken by random sampling technique, so that the IVA class in elementary school 7 Gianyar as the experimental group and the IVB class in elementary school 6 Gianyar as the control group with the total students in each group of 30 students. The data collection was done by the test method, the type of test was the usual multiple-choice objective test. The data obtained were analyzed using t-test analysis of separated variance. The result of data analysis is tcount = 7.067> ttable = 2,000 at 5% significance and dk = 58, then H0 is rejected and Ha accepted. The average value of science knowledge competence of the experimental group X Ì… = 0,46 , while average science knowledge competence of control group X Ì… = 0,26. Based on the results of this research, it can be concluded that the Reciprocal Teaching learning model based on performance assesment affect the knowledge competence of science students fourth grade students of elementary school Gugus I Gianyar districts year 2017/2018